Alterations in Blood Plasma Metabolome of Patients with Lesniowski-Crohn's Disease Shortly after Surgical Treatment-Pilot Study - Idkowiak, Jakub; Kubiak-Tomaszewska, Grazyna; Gatarek, Paulina; Marczak, Laukasz; Kaluzna-Czaplinska, Joanna; Tarnowski, Wieslaw; Uryszek, Mariusz; Bobrowska-Korczak, Barbara (MDPI, 2022)
Lesniowski-Crohn's disease (CD) is a type of chronic inflammatory bowel disease (IBD) of uncertain etiology. Initially, pharmacological management is undertaken; however, surgical intervention is necessary to improve life quality and relieve symptoms in most cases. Here changes are reported in blood metabolome that occurred three days after the ileo-colic region resection in the case of seven patients. Alterations are observed in levels of metabolites associated with multiple mitochondrial pathways, based on the Metabolite Set Enrichment Analysis, reflecting a high energy demand in the post-operative period. As most of these metabolites are also essential nutrients supplied from foods, we believe that our results might contribute to the discussion on perioperative nutrition's role in enhanced recovery.
Změny v metabolomu krevní plazmy u pacientů s Lesniowski-Crohnovou chorobou krátce po chirurgické léčbě – pilotní studie
Keywords: Gas Chromatography-Mass Spectrometry; metabolomics; blood plasma; Lesniowski-Crohn's disease; Plynová chromatografie-hmotnostní spektrometrie; metabolomika; krevní plazma; Lesniowski-Crohnova choroba